A prospective, randomized, double-blinded, split-face pilot study comparing Q-switched 1064-nm Nd:YAG versus 532-nm Nd:YAG laser for the treatment of solar lentigines. (17th November 2018) - Bohnert, Krista; Dorizas, Andrew; Sadick, Neil
ABSTRACT: Treating photoaging with laser technologies has increased in popularity due to their efficacy, minimal downtime, and side effects. New Q-Switched (QS) Nd:YAG lasers' frequency doubled with 532 nm wavelength can both target epidermal chromophores as well as stimulate collagen production. The objective of this study was to compare single-pulsed 1064-nm Nd:YAG with dual-pulsed 532-nm/1064-nm QS laser for reducing solar lentigines. Ten subjects with solar lentigines were enrolled in this prospective, randomized, double-blind, split-face study. Subjects received six laser treatments (half-face dual, half single) at 2-week intervals. Blinded investigator and subject assessments were conducted 1 month posttreatment to evaluate global skin improvement, safety, and patient satisfaction. Blinded investigator assessments showed statistically significant improvement in the dual-treated side. Patient satisfaction was also statistically significantly increased in the dual-treated side. In conclusion, dual laser treatment can result in superior and safe global improvement of photoaging.